Use of a microbial supplement containing live bacteria Bacillus subtilis and their metabolites in dairy farming - O. Yu. Oparina; A. S. Krasnoperov; S. V. Malkov; A. I. Belousov; A. E. Chernitskiy; I. Yu. Vershinina (Ветеринария сегодня)
The purpose of the research was to study parameters of immune status and milk yields in those cows that received a bacterial supplement containing live bacteria Bacillus subtilis strains B-239906 and B-249909 and their metabolites during a transition period. Animals in the experimental groups (10 animals in each) received the microbial supplement according to the following schemes: 14 days before calving (group 1), 14 days after calving (group 2), 14 days before and 14 after calving (group 3). Group 4 (n = 10) was a control one. On day 14 and day 28 after calving, the relative level of T-lymphocytes in blood of control cows and experimental group 2 did not significantly change compared with the level observed on day 1 after calving. While in groups 1 and 3, this indicator increased by 1.2–1.6 times throughout the whole experiment. In all cow groups, B-lymphocyte dynamics during the observation period was similar, i.e. an increase by day 14 and a decrease by day 28. The phagocytic activity of neutrophils in animals of all groups changed slightly. At the same time, the phagocytic index increased by 2.5–3.2 times throughout the experiment, which indicated an increase in nonspecific resistance of the body. Peak milk yields were recorded in cows of all experimental groups on day 90 of lactation. The maximum level (32.17 ± 3.33 kg) was observed in group 3. Within 150 days of observations, the average daily milk yields in animals of the experimental groups were: 24.50 ± 4.15 kg in group 1; 25.07 ± 4.38 kg in group 2; 25.33 ± 2.52 kg in group 3 and 22.75 ± 8.82 kg in the control group. The mass fraction of milk fat in all groups had no statistically significant differences throughout the entire observation period.